Sodium content of bread from bakeries in Maputo, Mozambique: trends between 2012 and 2018 - Jessen, N (2020)
Objective:To assess the Na content and price of bread available in bakeries in the city of Maputo in 2018 and describe trends since 2012.Design:Cross-sectional evaluation of bread sold in twenty bakeries in the city of Maputo. Three loaves of white and three loaves of brown bread were collected from each bakery when available, and Na contents were quantified by flame photometry. To assess trends, samples of white bread collected in 2012 and analysed using the same methodology were compared with samples of white bread collected in 2018 from the same bakeries.Setting:City of Maputo, capital of Mozambique.Results:In 2018, the mean (range) Na content in mg/100 g of white and brown breads were 419·1 (325·4-538·8) and 389·8 (248·0-609·0), respectively. Non-compliance with Na targets in bread according to the South African regulation (<380 mg/100 g) was observed in 70 % of white and 43 % of brown bread samples. A total of twelve bakeries had samples evaluated in both 2012 and 2018; among these, the mean Na content in white bread decreased by just over 10 % - the mean difference (95 % CI) was 46·6 mg/100 g (1·7, 91·5); and there was a significant increase of 3·7-5·4 meticais in the mean price per 100 g of white bread.Conclusions:The Na content of bread available in bakeries in the city of Maputo decreased in recent years despite the absence of a specific regulation in Mozambique. (c) The Authors 2020.